PERBEDAAN PERSEPSI ANTARA SISWA SEKOLAH NEGERI DAN SWASTA TERHADAP PEMBELAJARAN GURU PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (STUDI PADA SISWA KELAS VIIIÂ DI SMP NEGERI 1 NGAWI DENGAN SMP MAâ€™ARIF NGAWI) - EKO SUSENO, YOYOK (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The roles of public and private school teachers are very essential in the teaching learning process. The fruitfulness of a teaching corresponds heavily on the role of a teacher, which is brings the students perception. The good perception in teaching learning process will influence the maximum achievement of teaching goals, then, the perception should be supported by the interest and the motivation of the relation students. The goal of such research was to get information from the students’ of SMPN 01 Ngawi and the students of SMP Ma’arif Ngawi toward the teaching of sport and physical education teachers. In this research, the researcher used descriptive qualitative method ( non experiment).  The variable of the research were the students’ perceptions ( independent variable) and the teaching of the sport and physical education teachers ( dependent variable). The population of the research were the entire students of VIII grate of SMPN 01 Ngawi and SMP Ma’arif Ngawi. The sample of the research were VIII F and VIII G class of SMPN 01 Ngawi and VIII A and VIII B class of SMP Ma’arif Ngawi. There were a significant differentiation of the analysis result of the student’s perception toward  the teaching of sport and physical education teachers in the public and private junior high schools. The differentiation showed by the comparisons of t-hitung and t-tabel, which was t-hitung 3,176> t-tabel 1,645. For more information, we can also saw from the differentiation of the perception average mark. The average mark of the public school students were 43,78 and 41,71 for the private school students. Furthermore, we can conclude that there were perception differentiations between public and private school students in the teaching of sport and physical education teachers in SMPN 01 Ngawi and SMP Ma’arif. Keywords: Perception, the teaching of sport and physical education teachers in the public and private schools.